EVOLUTION OF WOMEN’S UNDERWEAR: GLOBAL AND UKRAINIAN CONTEXTS - Пашкевич, К. Л.; Герасименко, О. Д.; Сімак, А. І.; Чуботіна, І. М.; Монько, А. Л. (Art and Design, 2024)
Purpose. The purpose of the article is to study the historical development of twentieth-century underwear; to compare artistic and compositional features, types of cut, imaginative solutions and means of decoration of the period; to generalize modern trends in the evolution of underwear in the world and in Ukraine; to develop one’s own collection of underwear based on the results of the study. Methodology. To achieve this goal, an integrated approach was applied that combines the study of historical materials, systematic information and visual-analytical components. The illustrative material was developed using the graphic editor Xara Designer Pro. Results. The evolution of underwear is studied and the features of each decade of the twentieth century are characterized. The main trends in the development of underwear of the selected period of time are analyzed. It is determined that the global evolution differed from the Ukrainian one due to the peculiarities of the political regime under Soviet rule. However, after gaining independence at the end of the twentieth century, Ukraine actively joined the global underwear market. The following modern Ukrainian lingerie brands are characterized: Kingdom Angels, Pivovarova, Katimo, Fox Lingerie, Vrabrabra. Based on the research, the author has developed her own collection of lingerie, the creative source of which takes into account the main retro trends of women’s underwear of the twentieth century. Practical significance. The results of the research can be used in the educational process of training designers and the practical activities of contemporary fashion designers and fashion designers; in teaching disciplines on the history of design and fashion. In addition, the results of the research will contribute to the realization of the need to preserve and disseminate cultural heritage in the production of modern lingerie products.